PENGARUH PARTICIPATORY BUDGETING DAN INFORMASI ASIMETRIS TERHADAP BUDGETARY SLACK PADA BADAN PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPPKAD) KABUPATEN SUMENEP - Iqbal Rafiqi; Sri Kania Dewi Yana; Nabilatul Fitriyah (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2021)
In government organizations, the budget is a guideline for financial management in order to achieve goals. Budgeting is an important perspective for the public and private sectors. This study aims to determine the effect of participatory budgeting and information asymmetry on budgetary slack Â in the Regional Revenue, Financial and Asset Management Agency of Sumenep Regency. Sampling using purposive sampling method, totaling 27 structural employees. Data collection was done through a questionnaire. The analytical technique used in this research is regression analysis with IBM SPSS 20 software for windows.Based on the results of data management, it was obtained that the f-test significance value for the influence of participatory budgeting and information asymmetry on budgetary slack was 0.205 > 0.05. This proves that Ho3 is accepted and Ha3 is accepted. This means that there is no significant effect of budgetary participation and information asymmetry on budgetary slack in a negative direction. Thus, the participatory budget of subordinates and information asymmetry, the difference in information held by subordinates and superiors at the Regional Revenue, Financial and Asset Management Agency in Sumenep Regency does not really affect the existence of budgetary slack.